Towards a systematic climatology of sensitivities of Mediterranean high impact weather: a contribution based on intense cyclones - Homar, V.; Jansà, A.; Campins, J.; Genovés, A.; Ramis, C. (CCSD, 2007)
International audience One of the multiple approaches currently explored to mitigate the effects of hydro-meteorological hazardous events aims at improving the numerical weather forecasts. Under an ever increasing societal demand for cost cuts and more precise forecasts, targeted observations are currently receiving great attention within the operational weather community. The MEDEX project (http://medex.inm.uib.es) is aimed at improving the forecasts of high impact weather (HIW) in the Mediterranean and, in particular, proposes the creation of a climatology of sensitivities of such episodes. The construction of a comprehensive climatology of sensitivities is hampered by the lack of an exhaustive collection of Mediterranean HIW events. In this study we contribute with a systematic climatology of Mediterranean intense cyclones. We perform an objective cluster analysis of intense cyclones detected from the ECMWF ERA40 reanalysis using a k-means algorithm and compute the sensitivities for each of the resulting classes. For each cluster, a representative sensitivity field is computed using the MM5 Adjoint Modeling system. The results show that although the sensitive areas for intense Mediterranean cyclones are not particularly confined, it is remarkable how areas poorly sampled by the regular observing networks, such as North Africa, the Mediterranean Sea and the eastern North-Atlantic, are highlighted in the prototype sensitivity maps.